Democratic multiplicity : perceiving, enacting, and integrating democratic diversity - Tully, James, 1946- (Cambridge University Press, 2022)
This edited volume argues that democracy is broader and more diverse than the dominant state-centered, modern representative democracies, to which other modes of democracy are either presumed subordinate or ignored. The contributors seek to overcome the standard opposition of democracy from below (participatory) and democracy from above (representative). Rather, they argue that through differently situated participatory and representative practices, citizens and governments can develop democratic ways of cooperating without hegemony and subordination, and that these relationships can be transformative. This work proposes a slow but sure, nonviolent, eco-social and sustainable process of democratic generation and growth with the capacity to critique and transform unjust and ecologically destructive social systems. This volume integrates human-centric democracies into a more mutual, interdependent and sustainable system on earth whereby everyone gains.